Etnobotánica en el Alto Valle del Reno (Toscana y Emilia-Romaña, Italia) Etnobotanica nell'Alta Valle del Reno (Toscana ed Emilia-Romagna, Italia) - Egea Molines, Maria Teresa (Premio Tesi di Dottorato, 2018)
The Upper Rhine Valley (AVR) is borderland between the Italian regions of Tuscany and Emilia Romagna. The natural and cultural heritage based upon ethnobotanical knowledge in the AVR area has been studied, documented and analysed using semi-structured interviews. The information is presented through an ethnological and floristic catalogue, including both cultivated and wild species known to the local community. Although there is evidence of a great biocultural richness in the old oral tradition, important erosion phenomena threatening the conservation of ethnobotanical knowledge (immaterial culture) and associated plants (material culture) have been highlighted. The reasons behind the phenomena are partly due to the abandonment of agro-pastoral practices, as well as to the significant changes in the management of the territory and in the life forms.